Mitigating the Prevalence of Female Genital Mutilation and Cutting (FGM/C) in Ekiti State as a Panacea for Eradicating the Practice for Sustainable National Development in Nigeria - Asebiomo, Ayodele Mandela (Archives of Business Research, 2022)
This study sources for the prevalence of FGM/C practices in Ekiti State Nigeria in an effort to know the “why”, and “how” the practice can be reduce if not eliminated in our society. The population of the study comprised all child bearing adult women in all the sixteen Local Government Area of the State. Five Local Government Area Councils were randomly selected and 240 adult women were purposively selected from the five Local Government Area Councils at equal representation. Questionnaire named Female Genital Mutilation and Cutting Prevalence Questionnaire (FGMCPQ) developed by the researcher were used to collect data from the respondents. Frequency counts, percentage mean were used to answer research questions and Chi-square used to analyze the hypotheses formulated. The findings showed significantly the prevalence of FGM/C in all the Local Government Area Council covered. There are no significant differences on the prevalence across social and educational background. Cultural beliefs were significantly responsible for such practices with little or no religious undertone. But the practices showed significance practice in the rural area than the urban settlement. Many parents believes the practice reduce sexual urge among sexually active women and as a result recommends its practice. The study also showed that FGM/C can induce sexually transmitted infections, pelvic inflammatory diseases as well as recurring urinary tract infection. The study showed that FGM/C is often performed by a nonmedical practitioner with the aim of fulfilling cultural rites and most times for economic benefits. It was therefore recommends that thorough sensitization exercise should be carried out in both urban and rural area against FGM/C practices as regards to its health impact on girl child and in order to protect the female right in the society as well as enhancing national economic growth and development. Relevant laws should be enacted to punish erring individual families that engage in FGM/C practices in the society. More importantly, the circumcisers should ne provided by alternative source of income for their living.